Inferences of Diplodocoid (Sauropoda: Dinosauria) Feeding Behavior from Snout Shape and Microwear Analyses - Whitlock, John A. (Public Library of Science, 2011)
BACKGROUND: As gigantic herbivores, sauropod dinosaurs were among the most important members of Mesozoic communities. Understanding their ecology is fundamental to developing a complete picture of Jurassic and Cretaceous food webs. One group of sauropods in particular, Diplodocoidea, has long been a source of debate with regard to what and how they ate. Because of their long lineage duration (Late Jurassic-Late Cretaceous) and cosmopolitan distribution, diplodocoids formed important parts of multiple ecosystems. Additionally, fortuitous preservation of a large proportion of cranial elements makes them an ideal clade in which to examine feeding behavior. METHODOLOGY/PRINCIPAL FINDINGS: Hypotheses of various browsing behaviors (selective and nonselective browsing at ground-height, mid-height, or in the upper canopy) were examined using snout shape (square vs. round) and dental microwear. The square snouts, large proportion of pits, and fine subparallel scratches in Apatosaurus, Diplodocus, Nigersaurus, and Rebbachisaurus suggest ground-height nonselective browsing; the narrow snouts of Dicraeosaurus, Suuwassea, and Tornieria and the coarse scratches and gouges on the teeth of Dicraeosaurus suggest mid-height selective browsing in those taxa. Comparison with outgroups (Camarasaurus and Brachiosaurus) reinforces the inferences of ground- and mid-height browsing and the existence of both non-selective and selective browsing behaviors in diplodocoids. CONCLUSIONS/SIGNIFICANCE: These results reaffirm previous work suggesting the presence of diverse feeding strategies in sauropods and provide solid evidence for two different feeding behaviors in Diplodocoidea. These feeding behaviors can subsequently be tied to paleoecology, such that non-selective, ground-height behaviors are restricted to open, savanna-type environments. Selective browsing behaviors are known from multiple sauropod clades and were practiced in multiple environments.